2019
DOI: 10.3390/nu11030654
|View full text |Cite
|
Sign up to set email alerts
|

Tartary Buckwheat Extract Attenuated the Obesity-Induced Inflammation and Increased Muscle PGC-1a/SIRT1 Expression in High Fat Diet-Induced Obese Rats

Abstract: Obesity is intimately related to a chronic inflammatory state, with augmentation of macrophage infiltration and pro-inflammatory cytokine secretion in white adipose tissue (WAT) and mitochondrial dysfunction in skeletal muscle. The specific aim of this study is to evaluate effects of tartary buckwheat extract (TB) on obesity-induced adipose tissue inflammation and muscle peroxisome proliferator-activated receptor-γ coactivator (PGC)-1α/sirtulin 1 (SIRT1) pathway in rats fed a high-fat diet. Sprague-Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
(70 reference statements)
2
7
0
Order By: Relevance
“…Our findings are consistent with some previous studies demonstrating that schizophrenia patients with obesity and MetS displayed markedly elevated levels of proinflammatory factors (2,29,53,54). Interestingly, numerous studies have indicated that SIRT1 plays an important role in immune regulation, and the interaction between SIRT1 and immune inflammation is significantly related to metabolic abnormalities (55,56). We extended this association to show that the SIRT1 interacting with IL-6 as the influencing factor for the MetS in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with some previous studies demonstrating that schizophrenia patients with obesity and MetS displayed markedly elevated levels of proinflammatory factors (2,29,53,54). Interestingly, numerous studies have indicated that SIRT1 plays an important role in immune regulation, and the interaction between SIRT1 and immune inflammation is significantly related to metabolic abnormalities (55,56). We extended this association to show that the SIRT1 interacting with IL-6 as the influencing factor for the MetS in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 92%
“…23 It has been well-established that TB and TB extracts similarly regulated lipids and sugar in the blood, improved hepatic steatosis, and reduced adipocyte size. 13,24,25 This study systematically evaluated the STB roles in regulating hypolipidemia, alleviating insulin resistance function, and strengthening the liver, which are consistent with the previous study. 26 Given the evidence of abundant flavonoids in TB and STB, it can be speculated that flavonoids take charge of the regulation of blood lipids.…”
Section: ■ Discussionsupporting
confidence: 82%
“…PGC-1α plays a variety of physiological functions by combining with PPAR-γ, such as energy metabolism, glucose metabolism, inflammatory response and so on. [48][49][50] Studies have shown that up-regulation of PGC-1α and β could attenuate the energy metabolism disorder and inflammatory response in LPS induced septic heart failure mice. 51) Our study showed that NOR could up-regulate the expression of PGC-1α and PPAR-γ in LPS induced mice and RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%